Control of liver glucokinase activity: a potential new target for incretin hormones? - Francini, Flavio (2015)
We tested the exendin-4 and des-fluoro-sitagliptin effects on fructose-induced increase in liver glucokinase activity in rats with impaired glucose tolerance and the exendin-4 effect on glucokinase activity in HepG2 cells incubated with fructose in the presence/absence of exendin-9-39. After 3 weeks of in vivo fructose administration we measured: (1) serum glucose, insulin and triglyceride levels; (2) liver and HepG2 cells glucokinase activity and (3) liver glucokinase and 6-phosphofructo-2-kinase/fructose-2,6- biphosphatase mRNA and protein levels. Fructose fed rats had: hypertriglyceridemia, hyperinsulinemia and high liver glucokinase activity (mainly located in the cytosolic fraction) together with higher glucokinase and 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase mRNA and protein concentrations compared to control rats. Co-administration of either exendin-4 or des-fluoro-sitagliptin prevented serum and liver changes except glucokinase protein expression. Exendin-4 also prevented fructoseinduced increase in glucokinase activity in cultured HepG2 cells, effect blunted by co-incubation with exendin-9-36. In conclusion exendin-4/des-fluro-sitagliptin prevented fructose-induced effect on glucokinase activity, mainly affecting enzyme activity modulators. Exendin 9-39 blunted in vitro protective exendin-4 effect onglucokinase activity,thus suggesting a direct effect ofthe later onhepatocytes through GLP-1 receptor. Alterations of glucokinase activity modulators could play a role in the pathogenesis of liver dysfunction, becoming a potential new treatment target for GLP-1 receptor agonists